The nexus between nutrition and early childhood development - Alderman, Harold; Fernald, Lia (Annual Reviews, 2017)
This article looks at both nutrition and early childhood stimulation interventions as part of an integrated life cycle approach to development. We build on recent systematic reviews of child development, which are comprehensive in regard to what is currently known about outcomes reported in key studies. We then focus particularly on implementation, scaling, and economic returns, drawing mainly on experience in low- and middle-income countries where undernutrition and poor child development remain significant public health challenges with implications across the life course.